2006
DOI: 10.1210/en.2005-0600
|View full text |Cite
|
Sign up to set email alerts
|

Organ Messenger Ribonucleic Acid and Plasma Proteome Changes in the Adjuvant-Induced Arthritis Model: Responses to Disease Induction and Therapy with the Estrogen Receptor-β Selective Agonist ERB-041

Abstract: Two receptors [estrogen receptor (ER)alpha and ERbeta] mediate the manifold effects of estrogens throughout the body. Although a clear role has been established for ERalpha in the classical effects of estrogen activity, the physiological role of ERbeta is less well understood. A small-molecule ERbeta selective agonist, ERB-041, has potent antiinflammatory activity in the Lewis rat model of adjuvant-induced arthritis. To characterize the response of target organs and pathways responsible for this antiinflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 57 publications
1
29
2
Order By: Relevance
“…Our data, however, do not rule out any impact on airway smooth muscle hypertrophy/hyperplasia as suggested by others (Hughes et al, 2002). Indeed, considerable data have been published regarding the positive effects of ER␤ agonists in certain models of inflammatory disease (Harris et al, 2003Cristofaro et al, 2006;Follettie et al, 2006). However, a recent review indicated that ER␤ agonists are ineffective in a range of inflammatory models including collagen-induced arthritis (Harris, 2006).…”
Section: Discussioncontrasting
confidence: 69%
“…Our data, however, do not rule out any impact on airway smooth muscle hypertrophy/hyperplasia as suggested by others (Hughes et al, 2002). Indeed, considerable data have been published regarding the positive effects of ER␤ agonists in certain models of inflammatory disease (Harris et al, 2003Cristofaro et al, 2006;Follettie et al, 2006). However, a recent review indicated that ER␤ agonists are ineffective in a range of inflammatory models including collagen-induced arthritis (Harris, 2006).…”
Section: Discussioncontrasting
confidence: 69%
“…Thus, MIP-1 protein is a key player in the pathogenesis of several diseases (72). Earlier publications and preclinical studies from Wyeth clearly indicated the anti-inflammatory effects of ER-␤ ligands (58). As obesity is an inflammatory disease (9), induction of MIP-1 was not surprising considering the level of fat mass and body weight increase in vehicle-treated high-fat dietfed animals.…”
Section: Discussionmentioning
confidence: 99%
“…At present, no overall conclusion can be made about whether all ER␤ ligands will be diabetogenic. The ER␤ ligands developed by various pharmaceutical companies all appear to have tissue selectivity, and they may not all influence ER␤ in skeletal muscle (19,20). However, it might be a good precautionary measure to examine effects on GLUT4 early in the development of ER␤ agonists that are being developed to target disease.…”
Section: Discussionmentioning
confidence: 99%